HIF-1Alpha and NFIA_AS2 polymorphisms as potential determinants of total hemoglobin mass in endurance athletes - Malczewska-Lenczowska, J.; Orysiak, J.; Majorczyk, E.; Sitkowski, D.; Starczewski, M.; Zmijewski, P. (The Journal of Strength and Conditioning Research, 2022)
The aims of this study were to examine (1) the genotype distribution of rs11549465:C>T of the HIF-1a gene and rs1572312:C>A of the NFIA-AS2 gene; (2) the association between the genes and hematological status in endurance-oriented athletes; and (3) the association between the NFIA-AS2 gene and aerobic capacity in cyclists. Two hundred thirty-eight well-trained athletes (female n = 90, male n = 148) participated in the study. Total hemoglobin mass (tHbmass), blood morphology, intravascular volumes, i.e., erythrocyte volume (EV), blood volume (BV) and plasma volume (PV), and aerobic capacity indices, e.g., peak oxygen uptake (Vo2peak), and power at anaerobic threshold (PAT) were determined. In both studied genes, the CC genotype was predominant. In the HIF-1a gene, there were no differences in genotype and allele distribution among athletes from different disciplines and between sexes. The distribution of genotypes and alleles of the NFIA-AS2 gene differed significantly in male athletes; the frequency of A allele carriers (CA + AA) was significantly higher in cyclists than in rowers and middle- and long-distance runners. The athletes with CC genotype of NF1A-AS2 had significantly higher relative values of: tHbmass (total female athletes, cyclists), PV, BV (cyclists), and EV (total male athletes, cyclists) and PAT (cyclists) than A allele carriers (CA + AA genotypes). In conclusion, our study indicates that NFIA-AS2 rs1572312:C>A polymorphism was associated with hematological status in endurance athletes, as well as aerobic capacity indices in male cyclists. It suggests that this polymorphism may be a determinant of quantity of hemoglobin and intrtavascular volumes, which in turn can have an impact on aerobic performance.